Into the Wild - Krakauer, Jon (New York: Pan Macmillan, 1996)
In April 1992 a young man from a well-to-do family hitchhiked to Alaska and walked alone into the wilderness north of Mt. McKinley. He had given $25,000 in savings to charity, abandoned his car and most of his possessions, burned all the cash in his wallet, and invented a new life for himself. Four months later, his decomposed body was found by a moose hunter. How Christopher Johnson McCandless came to die is the unforgettable story of Into the Wild.
Keywords: Travelers$1 (BAlaska$1 (BBiographys -- Wilderness survival$1 (BAlaska$1 (BCase studiess -- Alaska$1 (BDescription and travels -- z